Olive Fruit Fly, Bactrocera oleae (Gmelin) (Insecta: Diptera: Tephritidae) - Howard V. Weems; James L. Nation (EDIS)
This document is EENY-113 (originally published as DPI Entomology Circular No. 44), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 1999. Revised: June 2003.